Homecare of confirmed COVID-19 cases in Nigeria: Current situation, challenges in implementation, and strategies for improvement - Olayinka Stephen Ilesanmi; Aanuoluwapo Adeyimika Afolabi (Journal of Interventional Epidemiology and Public Health)
Introduction: Health facility-based management has been inadequate to control COVID-19. This study aimed to assess the current situation of home-based care (HBC) of COVID-19 positives in Nigeria and implementation challenges, and strategies for its improvement. Methods: The study utilized a desk review and a qualitative data collection technique (key informant interview) for a situation analysis of COVID-19 HBC in Nigeria on 27th November 2020; nine months after the index case of COVID19 was reported in Nigeria. The study population were the COVID19 positives undergoing HBC. Epidemiologists, who had been deployed into the COVID-19 outbreak rapid response team, provided information on the study population. Six rapid responders were included from States with the highest COVID-19 case reports from each of the six geopolitical zones: Lagos, Gombe, Katsina, Delta, and Enugu States, and the Federal Capital Territory (FCT). The desk review and key informant interview informed on the comparative and normative needs, implementation challenges, and strategies for improvement. Results: The average age of the respondents was 45.90±4.52 years, 4 (66.7%) were males, and the average period of engagement in the COVID-19 outbreak response effort was 7.20±1.68 months. Lagos State has commenced COVID-19 HBC with less than 25% of positives managed. Their challenges include pre-care house visits. Enugu State has commenced COVID-19 HBC, with <25% of positives managed. Their challenges include inadequate personnel and poor surveillance. Delta State has commenced COVID-19 HBC with more than 50% of positives managed. Their challenges include inadequate information on contacts of COVID-19 positives. Gombe State has formally commenced COVID-19 HBC with less than 25% of positives managed. Their challenge is non-adherence to restriction guidelines. Katsina State has not formally commenced COVID-19 HBC, and over 50% of COVID-19 positives have been managed at home. Lack of COVID19 HBC documented policy and workforce are major gaps. The FCT has not formally commenced HBC, though more than 50% of COVID-19 positives have been managed at home. Their challenge is inadequate resources. Conclusion: HBC for the management of COVID-19 positives presents a promising strategy for the efficient management of COVID-19 cases in their homes without the associated overwhelming of the health system, thus support towards COVID-19 HBC in Nigeria should be promoted.